Clinical Evaluation of a Rapid Immunochromatographic Test for the Diagnosis of Dengue Virus Infection - Sang, Chew Theng (American Society for Microbiology, 1998)
A rapid immunochromatographic test was compared to the hemagglutination inhibition assay for separate determinations of dengue virus-specific immunoglobulin M (IgM) and IgG levels in paired serum specimens from 92 patients (34 with primary dengue virus infection, 35 with secondary dengue virus infection, and 23 without dengue virus infection). The rapid test showed 99% sensitivity in the diagnosis of dengue virus infection. The majority (30 of 34 [88%]) of patients with primary infection showed positive IgM but negative IgG, while 34 of 35 (97%) patients with secondary infection showed positive IgG with or without IgM. Specificity in nonflavivirus infections was 96% (1 of 23 positive). The rapid test should be a useful aid in rapid diagnosis of dengue virus infection.